Structural basis and function of the N terminus of SARS-CoV-2 nonstructural protein 1 - Zhao, Kaitao (2022)
Nonstructural protein 1 (Nsp1) of severe acute respiratory syndrome coronaviruses (SARS-CoVs) is an important pathogenic factor that inhibits host protein translation by means of its C terminus. However, its N-terminal function remains elusive. Here, we determined the crystal structure of the N terminus (amino acids [aa] 11 to 125) of SARS-CoV-2 Nsp1 at a 1.25-Å resolution. Further functional assays showed that the N terminus of SARS-CoVs Nsp1 alone loses the ability to colocalize with ribosomes and inhibit protein translation. The C terminus of Nsp1 can colocalize with ribosomes, but its protein translation inhibition ability is significantly weakened. Interestingly, fusing the C terminus of Nsp1 with enhanced green fluorescent protein (EGFP) or other proteins in place of its N terminus restored the protein translation inhibitory ability to a level equivalent to that of full-length Nsp1. Thus, our results suggest that the N terminus of Nsp1 is able to stabilize the binding of the Nsp1 C terminus to ribosomes and act as a nonspecific barrier to block the mRNA channel, thus abrogating host mRNA translation.